2016
DOI: 10.14738/assrj.311.2288
|View full text |Cite
|
Sign up to set email alerts
|

Effect Model Inquiry Training On Students Science Process Skill

Abstract: The aims of this study to analyze the science process skills that students are taught by inquiry training model better than students who use conventional learning. The research method is a quasi-experimental design with non-equivalent pretest-posttest Groups Experimental Design. Experimental class with inquiry learning model training and control class with direct learning model of instruction. The instrument used was a test of skill for science process skills. Data was analyzed using one way ANOVA. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Students need to get direct experience, making it easier for them to remember and understand the studied topics. Students become bored with following lessons, especially physics subjects, which are generally considered difficult by students (Harahap et al, 2016). Therefore it is necessary to change the learning model to be more effective so that students can be more active in learning activities.…”
Section: Introductionmentioning
confidence: 99%
“…Students need to get direct experience, making it easier for them to remember and understand the studied topics. Students become bored with following lessons, especially physics subjects, which are generally considered difficult by students (Harahap et al, 2016). Therefore it is necessary to change the learning model to be more effective so that students can be more active in learning activities.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the science process skill is needed for every student to provide life in the community. Ariani, Hamid, and Leny (2015); Handriani, Harjono, and Doyan (2016); Harahap, Manurung, Marbun, and Mihardi (2016) summarized that biology learning by implementing inquiry-based learning could improve students' science process skills and students' achievement at senior high school.…”
Section: Introductionmentioning
confidence: 99%
“…Harefa, et al (2016) revealed that the ability of students 'scientific knowledge of physics using inquiry training learning was better than the ability of students' scientific knowledge using direct instruction learning. Harahap, et al (2016) state that the learning process with the inquiry training model is able to create a scientific basis for students, develop creativity in solving problems and improve science process skills. Students are really placed as learning subjects, the teacher's role in teaching by inquiry training is as a mentor and facilitator.…”
Section: Introductionmentioning
confidence: 99%